2018
DOI: 10.1136/archdischild-2017-313199
|View full text |Cite
|
Sign up to set email alerts
|

‘So why didn’t you think this baby was ill?’ Decision-making in acute paediatrics

Abstract: Determining severity of illness and undertaking an adequate risk assessment is a fundamental part of acute paediatric practice. This review highlights physiology, communication, heuristics and external elements as factors which influence decision-making and discusses how incidence of disease and seniority of clinician impact might influence outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Positive experiences of care, across (n = 12) studies, were reported where parents were able to express their opinions’ on care given to their newborns and when there was good communication between providers and parents [ 22 , 26 , 33 , 34 ]. Positive interactions were evident when parents are taught basic nursing skills such as feeding, cleaning, clothing and monitoring their newborn,.…”
Section: Resultsmentioning
confidence: 99%
“…Positive experiences of care, across (n = 12) studies, were reported where parents were able to express their opinions’ on care given to their newborns and when there was good communication between providers and parents [ 22 , 26 , 33 , 34 ]. Positive interactions were evident when parents are taught basic nursing skills such as feeding, cleaning, clothing and monitoring their newborn,.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely all participants of this study relied on guidelines for severely unwell children and those in cardiac arrest regardless of experience. Decision tools in paediatrics are seldom as sensitive and specific as we would desire (Roland and Snelson, 2019)…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, all participants of this study relied on guidelines for severely unwell children and those in cardiac arrest regardless of experience. Decision tools in paediatrics are seldom as sensitive and specific as we would desire ( Roland & Snelson, 2019 ). Accuracy of gut feeling in clinical decision making is variable but shows potential for identifying sick children when compared with individual clinical features ( Van den Bruel et al, 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…14 The current diagnostic approach for sepsis rely predominately on clinician-guided assessment or physiologybased tools, which pose numerous challenges due to the complex nature of paediatric physiology. 15 While the search for more precise biomarkers for sepsis continues, little is known in relation to using concern as a diagnostic tool to aid in earlier recognition. 16 In addition to parental concern, the gut feeling or intuition of healthcare professionals may contribute to the recognition of sepsis.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%